Using A Genre-Based Approach To Improving Islamic University Students’ Writing Ability & Hots - Muhammad Guntur; Mustafa Mustafa (AT-TURATS, 2022)
This study aims to determine the effect of genre-based and conventional approaches on students' writing skills and HOTS. This study uses a quantitative design with a quasi-experimental method conducted at IAIN Palopo, South Sulawesi, Indonesia. Sixty-two students from two classes were selected as research participants by dividing them into two groups, namely the experimental and control groups. Data were collected using two instruments: the writing assessment rubric and HOTS. The data that has been collected is then analyzed quantitatively by running the MANOVA test on SPSS 24.00. The results showed that the genre-based approach in the experimental group outperformed the control group, which used the conventional method to improve students' writing skills and HOTS.